Solusi Produktif dalam Pemanfaatan Limbah Tahu - Oktaviany , Venny; Rofiah, Syahbaniar; Jaenudin, Jaenudin (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
The existence of waste in Indonesia is a common problem, environmental pollution to health problems. Tofu is a food product that is in demand by the Indonesian people. Community Service carried out at the Tempe and Tofu Cluster UMKM in Duren Jaya Bekasi by utilizing liquid and solid tofu waste so that it becomes economic value. There are three products produced in the PkM activity through the utilization of tofu waste, namely the manufacture of PIKAHU (Tofu Dregs Chips), gembus tempeh and PUKCAKBALAI (Soybean Waste Liquid Fertilizer). For further PkM activities, it can be sustainable and add technology to maximize the products produced.